Climate change, vulnerability and well-being in the Pacific region - Gounder R (Taylor and Francis Group on behalf of the New Zealand Association of Economists Incorporated, 2024)
The Pacific region has experienced vast adverse effects from climate change impacting the peoples’ livelihoods both in these nations’ urban and rural areas. Countries association between socio-economic performance and livelihoods have been adversity impacted by climatic hazards and vulnerabilities on nations’ economic performance impacting the societal outcomes. An assessment of the Pacific’s climate change, vulnerability and well-being is presented in general and a case study of Fiji in particular. The Pacific islands require resources invested in environmental education, and climate change and trade policy linkages to benefit the islands, future returns to individuals and higher levels of satisfied basic needs to reduce vulnerabilities.
Keywords: Climate change; vulnerability; wellbeing; Pacific; Fiji